Increased Serum IgG4 Associates with Asthma and Tissue Eosinophilia in Chronic Rhinosinusitis Patients - Ramezanpour, Mahnaz (Pathogens, 2020)
Chronic Rhinosinusitis (CRS) is a multifactorial disease where microorganisms’ innate and adaptive immunity can play a role. This study assessed the total IgG, IgG subclasses, IgE and IgA levels in serum samples from CRS and non-CRS control patients in relation to the disease severity, phenotype, histopathology and comorbidities. Total serum IgG, IgG1, IgG2, IgG3, IgG4 and IgE was determined from 10 non-CRS controls, 10 CRS without nasal polyp (CRSsNP) and 26 CRS with nasal polyp (CRSwNP) patients using ImmunoCap assays. Tissue lysates were analyzed for IgG levels by ELISA. Immunohistochemical analysis was used to measure the expression of IgE and IgG4 in tissue sections. The presence of anti-nuclear antigens (ANAs) against 12 autoantigens in sera and tissue lysates was determined by immunoblot assays. Total serum IgG/IgG1/IgG2 levels were higher in CRS patients vs. controls (p < 0.001), but were not different between CRSwNP and CRSsNP patients (p = 0.57). Serum IgG4/IgE levels were increased in CRSwNP patients compared to controls (p = 0.006), however, this relationship was attenuated by the inclusion of covariates. Serum IgG4 levels were more strongly associated with asthma (p = 0.038, exact median test) and tissue eosinophilia (Spearman’s rank rho = 0.51, p = 0.016) than IgE levels. No systemic ANAs were detected in any of the subjects tested. There was a polyclonal increase in serum immunoglobulins in CRS patients with elevated IgG4/IgE levels in CRSwNP patients having tissue eosinophilia and asthma.